Novel mechanisms for the synthesis of important secondary metabolites in Ginkgo biloba seed revealed by multi-omics data - He, Bing; Qian, Kun; Han, Xin; Li, Jianyang; Zhou, Qi; Xu, Li-an; Liu, Hailin; Cui, Peng (Frontiers in Plant Science, 2023)
Although the detailed biosynthetic mechanism is still unclear, the unique secondary metabolites of Ginkgo biloba, including ginkgolic acids (GAs) and terpene trilactones, have attracted increasing attention for their potent medicinal, physiological and biochemical properties. In particular, GAs have shown great potential in the fields of antibacterial and insecticidal activities, making it urgent to elucidate their biosynthetic mechanism. In this study, we systematically revealed the landscape of metabolic-transcriptional regulation across continuous growth stages of G. biloba seeds (GBS) based on multi-omics mining and experimental verification, and successfully identified all major types of GAs and terpene trilactones along with more than a thousand kinds of other metabolites. The phenological changes and the essential gene families associated with these unique metabolites were analyzed in detail, and several potential regulatory factors were successfully identified based on co-expression association analysis. In addition, we unexpectedly found the close relationship between large introns and the biosynthesis of these secondary metabolites. These genes with large introns related to the synthesis of secondary metabolites showed higher gene expression and expression stability in different tissues or growth stages combined with transcriptome and experimental validation results. Our results may provide a new perspective for the study of the regulatory mechanism of these unique secondary metabolites in GBS.